Water Quality Analysis of Gorewada Lake Water in Nagpur, India - Salahuddin (Geography, Earth Science and Environment: Research Highlights Vol. 1, 2024)
Gorewada Lake is positioned on the northwest corner of Nagpur city. It is the most alluring lake to visit. The proper control and appraisal of lake water condition and its purification is very crucial for appropriate care and management purposes. Water quality checking and investigation of the Gorewada Lake was implemented for numerous physico-chemical parameters in the month of June 2016. Water samples were collected in the morning hours from the selected sites of the lake in plastic containers to avoid unforeseeable changes in characteristics as per standard procedure American Public Health Association. These components are: (i) pH, (ii) Temperature, (iii) Electric Conductivity, (iv) Dissolved Oxygen, (v) Biochemical Oxygen Demand, (vi) Chemical Oxygen Demand, (vii) Total Phosphorous, (viii) Suspended Solid (ix) and Total Nitrogen respectively. The obtained values of each attribute have been compared with the standard values set by the World Health Organization (WHO). The results attained show that most of the attributes do not satisfy the permissible limit recommended by WHO. Hence the lake water is not suitable for drinking, bathing and other life-supporting activities.